Uma experiência didática com dobradura de papel e geometria das transformações no plano no ensino de matrizes no ensino médio - Freire, Veruska Bueno (2018)
The main objective of the international project The Klein Project of ICMI-IMU is to bring knowledge and applications of contemporary Mathematics to the enrichment of the knowledge of secondary school teachers, through small articles written in accessible language. This dissertation aims to face the bigger challenge of taking such knowledge into the classroom practice, studying the modern mathematical ideas that are not in the school textbooks in one Klein article about digital images and processing. Concrete teaching material has been constructed for paper-folding activities of a didactical sequence within the curricular content of matrices of secondary school level, with applications in the mathematical language of digital images, then promoting the understanding about the geometry of isometric transformations of plane. The work presents the planning of the sequence and the description of the execution of the lessons in actual classes, following the principles of Lesson Study methodology.